The effect of background knowledge on translation of lexical-meaning texts - Bui Nguyen Nguyet Minh (Journal of Technical Education Science, 2019)
Lexical meaning of the source language can be transferred to target language effectively when the translators have background knowledge of society – culture – experience comprehension. This is the essential thing in order to transfer the render of a message from a source language to target language in high-quality translation in which the connotation, figurative meanings, and cultural-equivalent words are used. The objective of this study was to investigate how background knowledge of the translators affect their translation competence by using lexical-meaning equivalence. The study was conducted on two groups of 40 participants who had different background knowledge: group A consists of HUFI (Ho Chi Minh University of Food Industry) employees and group B is Sai Gon University students. Participants are required to translate the lexical-meaning texts which related to translators’ prior knowledge. The data was collected by comparing the same translation texts done by groups A and B. The results indicated that there was a significant effect of translators’background knowledge on the quality of rendering. The perception of what they witnessed profoundly shapes the way they think and they tend to transfer their ideas across these perceptions. The implications of the results suggested that the perception of lexical meaning could be explained in details in every translation course